2009
DOI: 10.1093/eurheartj/ehp120
|View full text |Cite
|
Sign up to set email alerts
|

Pre-intervention eosinophil cationic protein serum levels predict clinical outcomes following implantation of drug-eluting stents

Abstract: This study shows for the first time an association between baseline ECP levels and the occurrence of MACEs in patients undergoing implantation of DES. Further studies are warranted to establish whether in this setting ECP is a risk marker or plays a contributory pathogenetic role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
38
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 40 publications
4
38
1
1
Order By: Relevance
“…ECP has been found to be associated with coronary atherosclerotic burden and with a poor clinical outcome after implantation of both bare metal and drugeluting stents. 9,10,26 In this study, we measured ECP in a population of STEMI patients at the time of PPCI. We found that serum levels of ECP predicted MACEs at 24 months, independently of baseline ejection fraction.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…ECP has been found to be associated with coronary atherosclerotic burden and with a poor clinical outcome after implantation of both bare metal and drugeluting stents. 9,10,26 In this study, we measured ECP in a population of STEMI patients at the time of PPCI. We found that serum levels of ECP predicted MACEs at 24 months, independently of baseline ejection fraction.…”
Section: Discussionmentioning
confidence: 99%
“…10,26 Our study is focused on an unselected coronary artery disease population and not focused on patients with previous history of allergic disease. Accordingly, median value of ECP (12.8 μg/L) in our population was lower than the upper normal limit (20 μg/L) recommended by allergologist.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Efforts toward identifying systemic biomarkers that could potentially be predictive of events or at least subjects at risk are most wanted. Recognizing the local nature of the processes, this may not be feasible, although encouraging data have recently been reported by Niccoli et al 7 Baseline plasma levels of eosinophil cationic protein, a marker of eosinophil activation, were shown to be predictive of future events after stent implantation. Several candidate markers addressing macrophage or T-cell activation could equally be studied sequentially.…”
Section: Future Researchmentioning
confidence: 99%